Global strategic management - Lasserre, Philippe (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2012)
"This book is designed as a core textbook for those students studying courses on Global Strategy and Strategic Management. It offers an insight into the impact of globalization on business organizations and how managers could and should react. It is written by a well-respected professor of strategy at one of the world's leading business schools and combines a strategic and managerial approach to global issues, blending theory and practical, empirical examples to great effect. Global Strategic Management embraces traditional strategic management teaching, but extends it to a world scale. New to this editi on: - More coverage of entrepreneurship and SMEs - Increased coverage of ethics, sustainability and the environment in chapter 15 on CSR - All "basic" strategy content revised and updated, with material on the financial crisis woven throughout - A section on similarities and differences between global strategic management and international business - A section on the impact of Web 2.0 and social networking in chapter 8 - All new, up-to-date mini case studies throughout - New end of chapter cases featuring an impressive spread of global companies, including some in the Far East and multinational corporations from emerging economies. These will come with case study questions and guideline answers on the updated companion website - More distinct pedagogy (chapter introductions, learning objectives, examples highlighted in the text) - More accessible language to ensure student friendliness and readability for ESL students - Improved 2 color page design - Improved pedagogy: learning objectives; mini examples; case studies; summary and key points; learning assignments; key words; web resources; references and further reading"--
Machine generated contents note: -- PART I: THE PROCESS OF GLOBALIZATION -- Globalisation of Markets and Competition -- Designing a Global Strategy -- Designing a Global Organization -- Global Strategic Alliances, M&As and Assessing Countries' Attractiveness -- Entry Strategies -- PART II: MANAGING GLOBALLY -- Global Marketing -- Global Operations -- Global Innovation -- Cross-cultural Management -- Global Human Resource Management -- Global Financial Management -- PART III: BROAD ISSUES IN GLOBALIZATION -- Emerging Global Powers -- The Social Responsibility of the Global Firm -- Global Trends.
Includes bibliographical references and indexes.
Keywords: International business enterprises -- Management; Strategic planning; Globalization -- Economic aspects; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / International / General; BUSINESS & ECONOMICS / Management